PENGARUH PENGGUNAAN METODE KOOPERATIF TIPE JIGSAW DAN K-W-L TERHADAP KEMAMPUAN MEMBACA TEKS REPORT SISWA KELAS IX SMP NEGERI 2 BALONGPANGGANG - Muntiani .; Rufi’i .; Hari Karyono (Jurnal Education and Development, 2019)
This study aimed to analyze the differences of the reading ability in text report in English between students who were taught using the cooperative learning of jigsaw and K-W-L method. This type of study was an experimental research with a pretest and posttest control group design. The population of this study was all students of class IX SMP Negeri 2 Balongpanggang Kabupaten Gresik with a total were 128 students. The sampling technique in this study was a simple random samling technique. The instrument for collecting data was a test which was used to measure the students’ reading ability in text reports. The data was analyzed by t-test. The results of t-test at 5% significance level indicated that the reading ability (posttest) between experiment group 1 and experiment group 2 has a t-count value of 2,140 (df = 50) greater than t-table (2,008) and probability value was 0,037 less than 0,05. Thus, there was a differences of readning ability in text report in English between student who was taught using the cooperative learning of jigsaw and K-W-L method where students were taught using K-W-L method have better scores than students were taught using jigsaw method. In addition, the results of the paired-samples t-test at the 5% significance level indicated that the probability value between the pretest and posttest of the reading ability was 0,000 < 0,05, so this means that there was an increase in the reading ability of text reports by 33,55% before and after the treatment of learning methods.